2019
DOI: 10.3389/fmicb.2019.00140
|View full text |Cite
|
Sign up to set email alerts
|

Natural Hosts and Genetic Diversity of the Emerging Tomato Leaf Curl New Delhi Virus in Spain

Abstract: Knowledge about the host range and genetic structure of emerging plant viruses provides insights into fundamental ecological and evolutionary processes, and from an applied perspective, facilitates the design and implementation of sustainable disease control measures. Tomato leaf curl New Delhi virus (ToLCNDV) is an emerging whitefly transmitted begomovirus that is rapidly spreading and inciting economically important diseases in cucurbit crops of the Mediterranean basin. Genetic characterization of the ToLCND… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
77
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(80 citation statements)
references
References 71 publications
2
77
1
Order By: Relevance
“…The begomovirus, Tomato leaf curl New Delhi virus (ToLCNDV), represents an important constraint to tomato production, in the Indian sub-continent. In recent years the virus has been rapidly spreading into several countries of the Mediterranean basin causing significant economic losses on cucurbit and tomato [188]. Recently, it has been recovered in Italy in pepper plants showing yellowing and leaf curling [189].…”
Section: Begomovirusesmentioning
confidence: 99%
“…The begomovirus, Tomato leaf curl New Delhi virus (ToLCNDV), represents an important constraint to tomato production, in the Indian sub-continent. In recent years the virus has been rapidly spreading into several countries of the Mediterranean basin causing significant economic losses on cucurbit and tomato [188]. Recently, it has been recovered in Italy in pepper plants showing yellowing and leaf curling [189].…”
Section: Begomovirusesmentioning
confidence: 99%
“…the pest has to be eradicated immediately if detected. However, the Panel notices the frequent report of outbreaks in Spain since 2013 (Table 3), and information from the literature suggesting that it might be more widespread in open field and in the environment than officially reported (Ju arez et al, 2019;Panno et al, 2019). 2017Source: EPPO GD, accessed on 24/2/2020.…”
Section: Pest Distribution In the Eumentioning
confidence: 99%
“…A monogenic resistance has been reported in a breeding line of sponge gourd (Islam et al, 2011) while in melon, five accessions were found to be resistant to ToLCNDV (Romay et al, 2019). In potato, the Indian cultivar Kufri Bahar is reported tolerant to the disease (Jeevalatha et al, 2017). Breeding efforts are ongoing and this option is seen as a major strategy over the long run, while its current applicability is still extremely limited Impact • In some hosts, symptoms may be confused with those caused by other begomoviruses;…”
Section: Availability and Limits Of Mitigation Measuresmentioning
confidence: 99%
“…Rich], smooth sowthistle (Sonchus oleraceus L.), false daisy [Eclipta prostrata (L.) L.], and apple of Sodom [Calotropis procera (Aiton) Dryand.] (Haider et al, 2006;Moriones et al, 2017;Zaidi et al, 2017;Juárez et al, 2019) have been found to be hosts of the virus, acting as reservoirs during the whole year.…”
Section: Introductionmentioning
confidence: 99%